PENGARUH QUESTIONS STUDENT HAVE TERHADAP HASIL BELAJAR MATERI MENGAPRESIASI KARYA SENI MUSIK KELAS VIII - Yohanes, Beni; Fretisari, Imma; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe background of Thisresearch was the effect of active learning type questions student have toward learning outcomes. In particular, the problem of this research wereâ€œHow is student learning outcomes on the material appreciate musical art, before giving learning type questions student have class VIII student, junior high school number four Teriak,Bengkayang regency ? How is student learning outcomes on the material appreciate musical art, after giving learning type questions student have class VIII student, junior high school number four Teriak, Bengkayang regency ? Is there any influence of learning type questions student have class VIII student, junior high school number four Teriak, Bengkayangregency ?. The purpose of this research was to know the effect of active learning type questions student have toward learning outcomes on the material appreciating musical art class VIII student, junior high school number four Teriak, Bengkayang regency. The theory used is active learning strategy, questons student have, and learning outcomes.Â Keyword: The influence of active learning, Type questions student have.